2015
DOI: 10.1074/jbc.m114.598581
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Regulates Osteoclastogenesis and Bone Metabolism in a Sex-dependent Manner

Abstract: Background: Caveolin-1 plays important roles in the regulation of diverse cellular responses. Results: Caveolin-1 knockdown reduced osteoclastogenesis in vitro, and caveolin-1 knock-out resulted in an increased and decreased osteoclastogenesis in male and female mice, respectively. Conclusion: Regulation of osteoclastogenesis by caveolin-1 was dependent on sex. Significance: This indicates a complicated, but critical, role of caveolin-1 in the regulation of bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…According to the results observed by X‐ray, the area of new bone formation at the bone‐tendon junction in the experimental group was larger than that in the control group. This result is consistent with other studies reporting that knockdown of caveolin‐1, due to the decrease in Receptor Activator of Nuclear Factor‐κ B Ligand (RNAKL), reduced osteoclastogenesis, which is one of the major producers for new bone resorption through reshaping bone and inhibiting pathological bone loss . On the other hand, the general findings from the experimental animals showed no fibrous proliferation in the experimental group but great fibrous proliferation was observed in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results observed by X‐ray, the area of new bone formation at the bone‐tendon junction in the experimental group was larger than that in the control group. This result is consistent with other studies reporting that knockdown of caveolin‐1, due to the decrease in Receptor Activator of Nuclear Factor‐κ B Ligand (RNAKL), reduced osteoclastogenesis, which is one of the major producers for new bone resorption through reshaping bone and inhibiting pathological bone loss . On the other hand, the general findings from the experimental animals showed no fibrous proliferation in the experimental group but great fibrous proliferation was observed in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with other studies reporting that knockdown of caveolin-1, due to the decrease in Receptor Activator of Nuclear Factor-κ B Ligand (RNAKL), reduced osteoclastogenesis, which is one of the major producers for new bone resorption through reshaping bone and inhibiting pathological bone loss. 15,16 On the other hand, the general findings from the experimental animals showed no fibrous proliferation in the experimental group but great fibrous proliferation was observed in the control group. Similar result has been revealed that the loss of caveolae protein in alveolar epithelial cells may result in a serious injury to type I pneumocytes in the process of fibrogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…In concert with M-CSF, RANKL enables OCG in vitro from primary OC progenitors (Quinn et al, 1998). While OCG in vitro can be induced by trace amounts (∼1 ng/ml) of sRANKL (Lin et al, 2007), commonly used concentrations of sRANKL are 10-200 ng/ ml (Lee et al, 2015;Uchiyama and Yamaguchi, 2004). Here, we show that TNFα (but not IL1β) is a potent inducer of OCG and adseverin in the absence of sRANKL, which is consistent with earlier data that TNFα, but not IL1β, can promote the differentiation of OC progenitors into mature, TRAcP-positive multinucleated cells in the absence of RANKL (Azuma et al, 2000;Fuller et al, 2006;Kim et al, 2005;O'Brien et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has a proapoptotic effect on osteoclasts. ERα deletion suppresses this effect in females, but not males, so that the Cav-1 effect might be due to a stronger dependency of estrogen signaling on Cav-1 in females ( 95 ). Sexually dimorphic effects of ER and Cav-1 and bone cancer metastasis are worthy of further mechanistic study.…”
Section: Literature Analysismentioning
confidence: 99%